2010
DOI: 10.1039/b918706e
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric properties of human islet amyloid polypeptide in liquid water

Abstract: The volumetric properties of human islet amyloid polypeptide (hIAPP) in water were studied in a wide temperature range by computer simulations. The intrinsic density rho(p) and the intrinsic thermal expansion coefficient alpha(p) of hIAPP were evaluated by taking into account the difference between the volumetric properties of hydration and bulk water. The density of hydration water rho(h) was found to decrease almost linearly with temperature upon heating and its thermal expansion coefficient was found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…It is worth noting that within our knowledge, only a few theoretical-computational studies on protein partial molecular volumes based on atomistic simulations have been attempted. [15][16][17][18][19] Such computational studies were based on isobaric-isothermal simulations (i.e. NpT ensemble) thus making hopeless 15 any reliable direct measure of the protein partial molecular volume.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that within our knowledge, only a few theoretical-computational studies on protein partial molecular volumes based on atomistic simulations have been attempted. [15][16][17][18][19] Such computational studies were based on isobaric-isothermal simulations (i.e. NpT ensemble) thus making hopeless 15 any reliable direct measure of the protein partial molecular volume.…”
Section: Introductionmentioning
confidence: 99%
“…Petrache et al [34] considered the volume of the peptide side chain a suitable parameter to understand the peptide-bilayer interaction and they showed the dependence of side chain volumes on the peptides location. Additionally, Brovchenko et al [41] demonstrated a direct correlation between the intrinsic peptide volumes and the number of intrapeptide hydrogen bonds (secondary structure content). They showed that the formation of these hydrogen bonds produces voids non-accessible for water, which contribute to an increased peptide volume.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent volume of a solute in solution from a molecular dynamics model can be calculated, by definition, as the difference between the volume of the model box containing the solution, and the volume of the model box containing the same amount of the pure solvent: 53,59,60…”
Section: Volumetric Characteristicsmentioning
confidence: 99%